Low-quality scientific evidence for the continuation of universal Vitamin A supplementation among under 5 children in India - Umesh Kapil; Aakriti Gupta (Wolters Kluwer Medknow Publications, 2016)
Vitamin A supplementation (VAS) is presently being undertaken in India among under 5 (U5) children for two possible benefits (i) to prevent nutritional blindness due to Vitamin A deficiency (VAD) and (ii) to reduce U5 mortality. The existing scientific evidence suggests that nutritional blindness due to VAD has been virtually eliminated and also the difference between U5 mortality rate and infant mortality rate is very low for VAS to have any meaningful impact. On the contrary, scientific evidence indicates that there could be side effects of the administration of mega dose of Vitamin A (MDVA). These side effects of MDVA have not been systematically investigated. The universal VAS should be discontinued immediately as there are no likely benefits to U5 children.